A comparative evaluation of dental caries status and salivary properties of children aged 5-14 years undergoing treatment for acute lymphoblastic leukemia, type I diabetes mellitus, and asthma - In vivo - Shreya Dubey; Sonali Saha; Abhay Mani Tripathi; Piyali Bhattacharya; Kavita Dhinsa; Deval Arora (Wolters Kluwer Medknow Publications, 2018)
Background: The subjective sensation of dry mouth, xerostomia, is a well-recognized problem in adults, however, relatively little attention has been paid to this issue in children. Xerostomia commonly occurs as an adverse effect of drugs in asthma and leukemia, which alter the composition and flow of saliva and systemic diseases, including diabetes. It decreases the oral pH and significantly increases the development of plaque and dental caries. Aim: This study aims to evaluate and compare the dental caries status and salivary properties of children aged 5-14 years undergoing treatment for acute lymphoblastic leukemia, type 1 diabetes mellitus, and asthma - in vivo. Materials and Methods: The study was divided into two parts: Part I: Oral examination was performed and dental caries status Decayed, Missing, Filled Teeth/ decayed, extraction, filled teeth (DMFT/deft) was noted and Part II: Salivary analysis was performed by GC Saliva-Check BUFFER kit to check for hydration, viscosity, pH of saliva, salivary flow, and buffering capacity. Statistical Analysis: All statistical analysis was performed using the SPSS 21 statistical software version. Inferential statistics were performed using Chi-square test and ANOVA. Post hoc pairwise comparison was done using Post hoc Tukey's test. Results: The prevalence of mean DMFT/deft with regard to salivary properties was highest in leukemic patients followed in descending order by diabetic and asthmatic patients. Conclusions: Leukemic patients had significantly higher caries and decreased salivary properties while asthmatic patients showed the least caries prevalence and best salivary properties.